2014
DOI: 10.17795/iji-21441
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison of Microscopic Method and Rapid Diagnostic Test in Detecting Plasmodium species

Abstract: Background: Since Iran is one of the malaria endemic areas, diagnosis of this disease is important. Although the microscopic study of stained peripheral blood smears is as a gold standard of malaria diagnosis, this method requires a microscope, the equipment, and trained people. Because of some problems associated with microscopic method in some situations, rapid diagnostic test (RDTs) can be a suitable alternative. Nevertheless, then diagnosis of malaria should be approved by microscopic Objectives: The rapid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 13 publications
(13 reference statements)
1
7
0
Order By: Relevance
“…Among the 28 articles included in the present study, 3 reported mixed infections by RDT type 2 (pf-HRP2/pan-aldolase) and microscopy 27 , 41 , 51 , 13 by RDT type 3 (pf-HRP2/pan-pLDH) and microscopy 19 , 21 , 27 , 28 , 30 , 31 , 33 , 35 , 38 , 40 , 43 , 44 , 47 , 3 by type 4 (Pf-LDH/pan-pLDH) and microscopy 34 , 36 , 51 , 1 by RDT type 5 (Pf/Pv-pLDH) 46 , and 9 by RDT type 6 (pf-HRP2/Pv-pLDH) 21 , 26 , 36 , 42 , 43 , 46 , 48 – 50 . Among 27 articles included in the present study, 1 reported mixed infections by RDT type 2 and PCR 32 , 5 on RDTs type 3 and PCR 21 , 28 , 33 , 43 , 45 and 5 by RDT type 6 and PCR 21 , 26 , 29 , 37 , 43 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the 28 articles included in the present study, 3 reported mixed infections by RDT type 2 (pf-HRP2/pan-aldolase) and microscopy 27 , 41 , 51 , 13 by RDT type 3 (pf-HRP2/pan-pLDH) and microscopy 19 , 21 , 27 , 28 , 30 , 31 , 33 , 35 , 38 , 40 , 43 , 44 , 47 , 3 by type 4 (Pf-LDH/pan-pLDH) and microscopy 34 , 36 , 51 , 1 by RDT type 5 (Pf/Pv-pLDH) 46 , and 9 by RDT type 6 (pf-HRP2/Pv-pLDH) 21 , 26 , 36 , 42 , 43 , 46 , 48 – 50 . Among 27 articles included in the present study, 1 reported mixed infections by RDT type 2 and PCR 32 , 5 on RDTs type 3 and PCR 21 , 28 , 33 , 43 , 45 and 5 by RDT type 6 and PCR 21 , 26 , 29 , 37 , 43 .…”
Section: Resultsmentioning
confidence: 99%
“…Ref. 47 Khorashad et al, 2014 Iran (2009–2010) Febrile patients (178) 52 47 5 Thick and thin blood films Malaria 102 (p.f/p.v) POCT kits (InTec Products Inc., China) pf-HRP2/pan-pLDH 3 40 35 5 a ND 17. Ref.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Much endeavors and progress has been made by the WHO to control and eradicate malaria (4). Iran is a malaria endemic area and malaria is regarded as a main health medical challenge in this area (5,6). Frequency of malaria has recently declined as a result of the endeavors of health establishments and specialists in Sistan and Baluchestan Province (5).…”
Section: Introductionmentioning
confidence: 99%
“…Iran is a malaria endemic area and malaria is regarded as a main health medical challenge in this area (5,6). Frequency of malaria has recently declined as a result of the endeavors of health establishments and specialists in Sistan and Baluchestan Province (5). Whereas parasite-based identification is growing, most doubted cases of malaria are not suitably diagnosed and thus disease monitoring continues to be obscure (7).…”
Section: Introductionmentioning
confidence: 99%